Maize revolution in West and Central Africa: an overview - Fakorede, M.A.B.; Badu-Apraku, Baffour; Kamara, A.Y.; Menkir, A.; Ajala, S.O. (2003)
Maize (Zea mays L.) is cultivated under a broad range of climatic conditions in West and Central Africa (WCA). Unfortunately, maize production is constrained by a host of abiotic and biotic stresses, including drought, low soil fertility, diseases, insect pests, and the parasitic weed Striga hermonthica. The stresses, which occur in all countries of WCA, are too formidable for individual national research programs to overcome. The West and Central Africa Collaborative Maize Research Network (WECAMAN) was inaugurated to develop and disseminate to farmers technologies that would overcome the production constraints. The technologies were developed in specific lead countries as well as IITA and evaluated in the relevant ecological zones of all WCA countries. The individual countries adopted the technologies that were suitable for their specific situations. Trends in land area under maize, total maize production, and yield per unit land area have shown dramatic increases in most of the WECAMAN member countries. Total maize production in the subregion has increased from about 2.74 million tons in 1980 to 10.5 million tons in 2000, a 384% increase. Maize production has caught up with, or surpassed sorghum and millet in much of the savanna areas of WCA. Apart from its use as human food and livestock feed, maize has become an important raw material for the flour milling, brewing, pharmaceutical, and starch-making industries in the subregion.